Traumatic Cerebral Infarction in Children: Case Report - Durukan, Polat; Kavalcı, Cemil; Yıldız, Mustafa (Fırat University, 2004)
Post traumatic cerebral infarction is seen as a complication of head trauma. In children many conditions like cerebral vasospasm, direct vascular compression due to mass effect, vascular injury, embolization and systemic hypoperfusion are thought to be responsible for cerebral infarction. But in half of the ischemic infarction cases in children, the reason was unexplained. An extensive evaluation is necessary for effective treatment of these children and to show the cause of the infarction. We aimed to remind trauma that is one of the cause of cerebral infarction which is rarely seen in children and to review the literature.

Post travmatik serebral enfarkt, kafa travmasının bir komplikasyonu olarak görülmektedir. Serebral vazospazm, kitle etkisine bağlı direkt vasküler kompresyon, vasküler yaralanma, embolizasyon ve sistemik hipoperfüzyon gibi birçok durum çocuklarda serebral enfarkt oluşumundan sorumlu tutulmaktadır. Buna rağmen çocuklardaki iskemik enfarktların yarısında altta yatan sebepler açıklanamamaktadır. Bu çocukların etkin tedavilerinin yapılması ve serebral enfarktın sebebinin belirlenmesi için geniş bir değerlendirme yapılması gerekmektedir. Amacımız çocuklarda nadir görülen serebral enfarktın nedenleri arasındaki travmanın akıldan çıkarılmaması gerektiğini hatırlatmak ve literatür bilgisini gözden geçirmektir.
Çocukta Travmatik Serebral Enfarkt: Olgu Sunumu